A Clinical Study to Evaluate the Efficacy of Conductive Method of Agnikarma with Suvarnadi Salaka in the Pain Management of Sandhigatavata (Osteoarthritis of Knee Joint) (AYUSHDHARA, 2025)
The conductive method of Agnikarma using Suvarnadi Shalaka has proven to be an effective treatment for Sandhigata Vata (osteoarthritis of the knee joint), a degenerative disorder characterized by pain, stiffness, and restricted joint mobility. This clinical study aimed to evaluate the efficacy of Agnikarma in pain management and functional improvement. A total of 30 patients diagnosed with knee osteoarthritis were treated with conductive method of Agnikarma once a week for four weeks. The results demonstrated a significant reduction in pain (85.32%), tenderness (89.75%), and crepitus (78.35%), along with improvements in joint mobility (extension: 55.87%, flexion: 10.89%). Statistical analysis confirmed these findings as highly significant (p < 0.0001). The treatment was well tolerated with no major adverse effects, offering a safe, minimally invasive, and effective alternative to conventional therapies. Agnikarma works by improving local circulation, reducing inflammation, and enhancing tissue healing, making it particularly beneficial for Vata-Kaphaja disorders. This study concludes that the conductive method of Agnikarma with Suvarnadi Shalaka is a promising approach for managing knee osteoarthritis, with further large-scale studies needed to establish its long-term efficacy.